2020
DOI: 10.1515/znc-2020-0126
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, antioxidant and antimicrobial activity of essential oils from tangerine (Citrus reticulata L.), grapefruit (Citrus paradisi L.), lemon (Citrus lemon L.) and cinnamon (Cinnamomum zeylanicum Blume)

Abstract: The phytochemical and biological properties of tangerine (Citrus reticulata L.), grapefruit (Citrus paradisi L.), lemon (Citrus lemon L.) and cinnamon (Cinnamomum zeylanicum Blume) essential oils were examined. The chemical composition of the essential oils determined using chromatography analysis revealed that D-limonene and cis-cinnamaldehyde were the main components. The antioxidant and antimicrobial activities of the essential oils have been studied by the DPPH radical-scavenging assay and the disc-diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 52 publications
5
45
0
5
Order By: Relevance
“…Results revealed that all the NL and PO EO analyzed showed antioxidant activity (Figure 4). This result is in accordance with other antioxidant studies of several Citrus EO, such as C. aurantium [40,41], C. aurantifolia [41], C. reticulata [8,40], C. sinensis [40], C. limon [40], C. lumia [42], and other Citrus species [43][44][45]. In our study, the values of antioxidant activity ranged from 5.03% ± 3.76 to 39.43% ± 5.39 for NL, and from 12.10% ± 4.99 to 31.54% ± 3.04 for PO, including all dates of the two seasons.…”
Section: Antioxidant Activity Of Nl and Po Eosupporting
confidence: 92%
“…Results revealed that all the NL and PO EO analyzed showed antioxidant activity (Figure 4). This result is in accordance with other antioxidant studies of several Citrus EO, such as C. aurantium [40,41], C. aurantifolia [41], C. reticulata [8,40], C. sinensis [40], C. limon [40], C. lumia [42], and other Citrus species [43][44][45]. In our study, the values of antioxidant activity ranged from 5.03% ± 3.76 to 39.43% ± 5.39 for NL, and from 12.10% ± 4.99 to 31.54% ± 3.04 for PO, including all dates of the two seasons.…”
Section: Antioxidant Activity Of Nl and Po Eosupporting
confidence: 92%
“…Recently, the antioxidant activities of Citrus reticulata, Citrus paradise, and Citrus lemon peels' essential oils were reported (Denkova-Kostova et al, 2020). The radical scavenging potential on DPPH radical revealed that the highest percentage of inhibition was found in the grapefruit (87.5%), followed by lemon and tangeretine with values of 86.1% and 78.0%, respectively.…”
Section: Antibacterial Potentialmentioning
confidence: 99%
“…The minimum inhibitory concentration of grapefruit essential oil was determined to be 100 mg/l after a 2-day incubation of Aspergillus fumigatus [43]. Tangerine essential oil exhibited a wide anti-fungal spectrum inhibiting the growth of Aspergillus fumigatus, Aspergillus terreus, Alternaria alternata, Fusarium oxysporum, Penicillum italicum and Trichoderma viride at 750 ppm of oil in PDA medium [44]. After 14 days of incubation, Aspergillus flavus growth was inhibited to 18.70% in response to lemon essential oil, and 5.92% to orange essential oil.…”
Section: Discussionmentioning
confidence: 99%